Differential impacts of jogging and rope skipping in college students in China based on physical test score: a randomized controlled trial baseline indicator comparison in the intervention - Chen, Yuxuan; Wu, Junjie; Xu, Zhuo; Chen, Rucheng; Sun, Qinghua (Frontiers in Public Health, 2025)
IntroductionStudying the differential effects of jogging and rope skipping provides useful insights for teens, adolescents, and even adults to make choices and maintain healthy physical activities, which may also have positive significance for the promotion of public physical fitness and health.MethodsA total of 92 college students were enrolled in the study and randomly divided into jogging group, rope skipping group and control group. Tests and questionnaires were conducted before and right after the intervention, and a questionnaire survey was conducted again half a year after the intervention.ResultsThe results showed that the standing long jump performance and the cardiopulmonary function in the jogging group were significantly improved after the intervention, the average score of standing long jump increased from 72.00 to 76.45 and the mean systolic blood pressure decreased from 125.07 to 121.24 (t = 3.048, 2.139, p = 0.005, 0.041). The scores of 800 or 1,000 meters and the total scores of physical test in the rope skipping group and the control group were decreased significantly. The improvement of standing long jump performance in the jogging group was significantly higher than that in the control group.DiscussionThe main reason for the decline in the rope skipping group may be due to insufficient strength. Jogging differs from rope skipping in terms of muscle focus, arm-swinging style, nature of the exercise, and the associated exercise mood. As a result, after short-term training, jogging has a more positive significance than skipping rope in maintaining and improving physical fitness and cardiopulmonary function. If you want to improve your physical fitness in a shorter period of time, then jog.